2014
DOI: 10.1097/brs.0000000000000447
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Artery Anomalies at the Craniovertebral Junction in the US Population

Abstract: N/A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 13 publications
3
26
0
Order By: Relevance
“…The C-1 LMS is a common method for C-1 fixation but it is technically demanding, especially when the lateral mass is obscured by a thick posterior arch, 39 ponticulus posticus, 17 anomalous VA, 17,28,35,37 or a large paravertebral venous plexus. 21 Goel et al reported 2 patients who required an alternative method and only 1-side LMS was completed in 9 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-1 LMS is a common method for C-1 fixation but it is technically demanding, especially when the lateral mass is obscured by a thick posterior arch, 39 ponticulus posticus, 17 anomalous VA, 17,28,35,37 or a large paravertebral venous plexus. 21 Goel et al reported 2 patients who required an alternative method and only 1-side LMS was completed in 9 cases.…”
Section: Discussionmentioning
confidence: 99%
“…7,21,39 If C1-2 was displaced after injury, the PS may exhibit stronger resistance. It was also shown that the incidence of a VA anomaly between C-1 and C-2 in Asia was more common than in the US, and it directly affected the safety of C-1 LMS placement, 17,28,35,37 so fixation must be planned to minimize the VA injury. The choice was also influenced by our clinical experience.…”
Section: 4mentioning
confidence: 99%
“…The CT angiographs were reviewed according to the method provided by O'Donnell et al [4]. Vertebral artery was considered hypoplastic if it was half or less of the diameter of its counterpart.…”
Section: Anatomical Variantsmentioning
confidence: 99%
“…Recently, conflicting data on the incidence of these anomalies have been published. Asian-based studies show high incidence of 10 % of the anomalous course of the vertebral artery at the craniocervical junction [2,3], whereas the North American study identifies these anomalies in less than 1 % of patients [4]. This difference has implication for the need for the preoperative vascular imaging in various ethnical groups of patients scheduled for the above-mentioned procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The vertebral artery's third segment, as well as the presence of other elements, such as the venous cervical plexus, cervical nerve roots, the atlantooccipital membrane, and the dura in addition to the risk of failure related to the fixation makes every surgical manipulation critical for an optimal radiographic and clinical outcome. [1][2][3][4][5][6] Indications for C1-C2 posterior fixation include instability caused by degenerative diseases and infections, as well as trauma, tumors, congenital malformations, and os odontoideum. 6,7 Several C1-C2 posterior fixation surgical techniques and their modifications are frequently applied.…”
Section: Introductionmentioning
confidence: 99%